Posterior reversible encephalopathy syndrome after anlotinib treatment for small cell lung cancer: A case report and literature review - Zou, Xiaomeng; Zhou, Peng; Lv, Wei; Liu, Chuanyong; Liu, Jie (Frontiers in Pharmacology, 2023)
Anlotinib is an oral multi-targeted tyrosine kinase inhibitor as a third-line and subsequent treatment for patients with small cell lung cancer (SCLC) in China. The neurotoxicity is less reported. Posterior reversible encephalopathy syndrome (PRES) is characterized by headaches, seizures, encephalopathy, and visual disturbances, as well as focal reversible vasogenic edema seen on neuroimages. Here, we presented a case of PRES in a small cell lung cancer (SCLC) patient associated with anlotinib. A 37-year-old female patient, who had a history of diabetes, with extensive-stage SCLC received anlotinib after third-line chemotherapy. Ten cycles of anlotinib later, the patient experienced visual disturbance and was diagnosed with PRES based on the typical demyelination of white matter obtained in the brain magnetic resonance. During anlotinib therapy, the patient did not develop anti-VEGF therapy-induced hypertension. Subsequently, the patient stopped anlotinib, but she did not recover from symptoms. We also summarized the characteristics of fifty-four cases of PRES caused by antiangiogenic drugs in the literature. Based on our experience and the literature review, the incidence of PRES induced by antiangiogenic drugs is low, and the symptom can resolve upon stopping the medications. However, some cases still have a poor prognosis and the underlying mechanism requires further investigation. In addition, early detection and treatment of PRES are essential for physicians.